Chloride anion transporters inhibit growth of methicillin-resistant Staphylococcus aureus (MRSA) in vitro - Share, Andrew I.; Patel, Khushali; Nativi, Cristina; Cho, Eun J.; Francesconi, Oscar; Busschaert, Nathalie; Gale, Philip A.; Roelens, Stefano; Sessler, Jonathan L. (Chemical communications (Cambridge, England), 2016)
A series of aminopyrrolic receptors were tested as anion transporters using POPC liposome model membranes. Many were found to be effective Cl − transporters and to inhibit clinical strains of Staphylococcus aureus growth in vitro . The best transporters proved effective against the methicillin-resistant Staphylococcus aureus (MRSA) strains, Mu50 and HP1173. Tris-thiourea tren-based chloride transporters were also shown to inhibit the growth of S. aureus in vitro .